OPTIMALISASI LAPORAN KEUANGAN DALAM MENINGKATAN OMZET BAGI UMKM DI KABUPATEN BOGOR - Jasmadeti Jasmadeti; Nilda Tartilla; Amrulloh Amrulloh (LPPM Institut Pendidikan Nusantara Global, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Bogor Regency contribute significantly to the regional economy. However, they frequently encounter challenges in achieving optimal financial management, particularly in the preparation of accurate and relevant financial statements. This situation impedes their ability to comprehensively assess business performance and consequently hinders efforts to enhance turnover. Sound financial reporting is not merely an administrative requirement; it also provides critical information for strategic decision-making, attracting potential investors, and securing access to funding. This study investigates the optimization of financial reporting as a means to improve turnover for MSMEs in Bogor Regency. Optimization strategies include the provision of training and mentoring programs. Furthermore, the availability of robust financial statements enables MSMEs to pursue business development opportunities through capital acquisition and integrated digital marketing initiatives. Approaches to optimizing MSME financial reporting involve enhancing accounting literacy, implementing appropriate accounting standards (SAK EMKM), and leveraging information technology in the preparation of financial statements. By improving their financial reporting practices, MSMEs can better analyze sales performance, identify opportunities for enhanced efficiency, and develop more effective marketing strategies, ultimately leading to sustained increases in turnover.